High-gravity-assisted scalable synthesis of zirconia nanodispersion for light emitting diodes encapsulation with enhanced light extraction efficiency. (23rd February 2019) - He, Xianglei; Wang, Zhi; Pu, Yuan; Wang, Dan; Tang, Ruijie; Cui, Simin; Wang, Jie-Xin; Chen, Jian-Feng
Highlights: A high-gravity-assisted method for efficient synthesis of zirconia nanoparticles. Highly dispersed zirconia nanoparticles in organic solvents and epoxy resin. Significant enhanced light extraction efficiency of LEDs by zirconia nanodispersion. Abstract: Zirconia-based hybrid polymers has become one of the ideal encapsulation material for light emitting diodes (LEDs) with high extraction efficiency due to their proper refractive index to those of semiconductor chips. However, the controlling of the dispersion for zirconia nanoparticles in polymeric hosts to obtain optically transparent hybrid nanocomposites has been one of the major challenges. Herein, we reported the synthesis of zirconia nanodispersion via high-gravity-assisted homogeneous precipitation in an internal circulation rotating packed bed (RPB) reactor followed by two-step modification. An alternative to conventional precipitation in batch stirred tank reactors (STR), the process intensification by high-gravity RPB results in homogeneous micromixing during the nucleation and growth of zirconia particles, which are benefit for continuous and reproducible production of ultrasmall zirconia nanoparticles. The obtained zirconia nanoparticles are purely cubic phase with narrow size-distribution in the range of 3–5 nm according to the X-ray diffraction and transmission electron microscopy characterization, which were similarity to that by the conventional methods. Nevertheless, the average hydrodynamic diameters of zirconia nanoparticles in aqueous solutions obtained by RPB methods were much smaller than those prepared in conventional STR, which enabled easy control and surface modification for highly dispersed nanodispersion in organic solvents and/or polymeric hosts. After two-step surface modification, zirconia nanoparticles with goal-directed structures were obtained, with highly dispersity in various organic solvents (e.g. toluene, trichloromethane, tetrahydrofuran, etc.) and aliphatic epoxy resin, forming transparent hybrid films with tunable refractive indexes. The preliminary applications of these zirconia nanodispersions for LEDs encapsulation were demonstrated. The light extraction efficiency of the LEDs devices packaged with zirconia/epoxy hybrid material increased by 10 percent when the doping content of zirconia nanoparticles was 0.2, compared to the devices encapsulated by original epoxy.